Tolerance, Variability and Pharmacokinetics of Albumin-Bound Paclitaxel in Chinese Breast Cancer Patients - Li, Qingmei; Zhang, Hong; Zhu, Xiaoxue; Liu, Chengjiao; Wu, Min; Li, Cuiyun; Li, Xiaojiao; Gao, Lei; Ding, Yanhua (Frontiers in Pharmacology, 2018)
Objective: The aim of this study was to explore the tolerance, variability, and pharmacokinetics (PK) of albumin-bound paclitaxel (QL, HR, ZDTQ) in Chinese breast cancer patients. Methods: Three randomized, open-label, two-period crossover bioequivalence studies were conducted with albumin-bound paclitaxel. Each subject received a single dose of 260 mg/m2 albumin-bound paclitaxel (sponsor 1 [QL, light food], sponsor 2 [HR, fasting], sponsor 3 [ZDTQ, light food]; test) or Abraxane® (reference) and was monitored for 72 hours. Serum concentrations of total paclitaxel and unbound paclitaxel were measured using liquid chromatography/mass spectrometry (LC/MS), and appropriate pharmacokinetic parameters were determined by non-compartmental methods. Safety assessments included adverse events, hematology and biochemistry tests. Results: The bioequivalence analyses of the QL, HR and ZDTQ products included 24, 23 and 24 patients, respectively. The mean t1/2 was 20.61–27.31 hours for total paclitaxel. Food intake did not affect the pharmacokinetics of paclitaxel. From the comparison of total paclitaxel and unbound paclitaxel, the 90% confidence intervals (CIs) for the ratios of Cmax, AUC0-t, and AUC0-∞ were within 80.00%–125.00%. The intra-subject variability ranged from 6.4%-11% and 9.85%-15.87% for total paclitaxel and unbound paclitaxel, respectively. Almost all subjects in the test and Abraxane® (reference) groups experienced mild or moderate adverse events. No fatal AEs or study drug injection site reactions related to these drug were observed. Conclusion: Albumin-bound paclitaxel (QL, HR or ZDTQ; test products) showed bioequivalence to Abraxane® (reference) with lower intra-subject variability and less than 16% in all cases, and were well-tolerated in Chinese breast cancer patients. 22 patients is enough for Albumin-bound paclitaxel bioequivalence study.